Saken Seifullin and the introduction of the Kazakh language in office work - Kassimova, S.S.; Temirgaliev, K.A.; Nugman, B.; Smagulov, N.B. (Акад. Е.А. Бөкетов ат. Қарағанды ун-ті КЕАҚ баспасы, 2023)
The article is devoted to an important trend in the social and political life of the Kazakh AKSR in the early 1920s — the issue of doing office work in the Kazakh language. The activity and contribution of S. Seifullin, the chairman of the Council of People’s Commissars of the Kazakh SSR, to the adoption of the decree of the Kazakh Central Executive Committee on November 22, 1923 “On introduction of proceedings in the Kazakh language” and its implementation was analyzed. It was determined that the process of transfer to the Kazakh language in the provincial, district, volost institutions was difficult, and the differences of opinion of the people's commissariats of the Kazakh government on the issue were determined. The effectiveness of S. Seifullin's activities and work organization methods in finding a way out of the impasse and solving the problem is shown. S. Seifullin's civil, patriotic image was revealed through the analysis of his articles and thoughts related to the development of the Kazakh language. It was concluded that transfer to the Kazakh language laid the foundation for national progress, renewal and educational, cultural and spiritual development of the Kazakh people.
Сəкен Сейфуллин жəне қазақ тілінде іс жүргізуді енгізу
Сакен Сейфуллин и внедрение казахского языка в делопроизводство
Keywords: maternity leave; national policy; Kazakh language; education; culture; office work; volost institution